PENGEMBANGAN DAN VALIDASI METODE PENETAPAN KADAR ASPIRIN DAN PARASETAMOL DALAM TABLET KOMBINASI DAN PUYER MENGGUNAKAN FOURIER-TRANSFORM INFRARED (FTIR) - Chintya, Lidya
Fourier-Transform Infrared (FTIR) is a common method to identify and verify the functional groups in a compound. This research was tried to be used FTIR as a quantitative method for assay of aspirin and paracetamol. Aspirin and paracetamol is an antipyretic-analgesic drug. The purpose of this study is to develop FTIR as method for assay combination dosage form. Percent transmission spectrum changed into an absorbance spectrum, then has been obtained calibration curve for checking the linearity. The next step was conducted the validation method included specificity, linearity, accuracy, precision, range, limit of detection, and limit of quantification. After that, measured the content two kind of dosage form from the market that was tablet and powder. The specific wavenumbers for aspirin was C=O functional group at 1754.9 cm -1 and for parcetamol was C-N functional group at 1562.06 cm -1 . Validation parameters for aspirin: regression equation y = 0.22x + 0.0962, r = 0.9995, Vxo = 1.33%, percent recovery 99.77 –100.45 %, intra-day precision 0.86, 1.06, 0.81%, inter-day precision 0.83%, limit of detection 0.09%, and limit of quantitation 0.3%. And then for paracetamol showed regression equation y = 0.17x + 0.2366, r = 0.9994, Vxo = 0.5%, percent recovery 99.89 –100.53 %, intra-day precision 1.52, 1.06, 1.25%, inter-day precision 0.43%, limit of detection 0.05%, and limit of quantitation 0.17%. The method of assay aspirin and paracetamol in a combination dosage form can be performed use FTIR. The method has been validated and can be proposed as an alternative method.